Club and players' pressures on the motivation, vitality and stress of development coaches - Alcaraz, S.; Viladrich, C.; Torregrosa, M.; Ramis, Y.; Gillham, A. (International Journal of Sports Science and Coaching, 2015)
Drawing from self-determination theory, the purpose of this study was to examine how environmental factors predict coaches` intrinsic motivation and amotivation, which in turn were expected to be related to coaches` subjective vitality and stress. Development coaches (n = 311) completed a questionnaire tapping the targeted variables. Structural equation modelling supported a model in which opportunities for professional development and perceptions of players` intrinsic motivation were positively related to coaches` intrinsic motivation and negatively associated to coaches` amotivation. In turn, intrinsic motivation predicted subjective vitality whereas amotivation led to suffering from stress. Our results highlight how coaching environments influence coaches` motivation and psychological health. The study discusses two conditions that could help clubs at developmental level to maintain their coaches intrinsically motivated: Providing coaches with opportunities for learning and improvement, and being aware of the reciprocal relationship between coaches` and players` motivations.